THE BOTANY OF SOMERSET ISLAND, DISTRICT OF FRANKLIN - Savile, D. B. O. (Canadian Journal of Botany, 1959)
The geology, physiography, general appearance, climate and weather, and history of exploration of Somerset I. are discussed briefly. The principal habitats and the areas visited are described. Data are presented on prevailing winter wind directions on Somerset I. and Boothia Pen., drawn from observations on residual snowbanks and plant growth. A few phenological data are presented, which supply further evidence that spring development at low arctic sites lags behind that at both subarctic and high arctic sites. Annotated lists are given of the fungi (28 species) and vascular plants (90 species) collected. Among the fungi Puccinia helicalis sp. nov. on Pedicularis capitata, and Doassansia nearctica sp. nov. on Ranunculus hyperboreus are described; and Exobasidium warmingii, intermediate between Exobasidium and Kordyana, is made the type of Arcticomyces gen. nov. Thirty-two species of vascular plants are added to the recorded flora of the island.